2019
DOI: 10.1186/s13063-019-3531-0
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative complications and nutritional status between uncut Roux-en-Y anastomosis and Billroth II anastomosis after D2 distal gastrectomy: a study protocol for a multicenter randomized controlled trial

Abstract: Background Gastric cancer is the fourth most common malignant disease worldwide, with lower one-third gastric cancer the most common type. Distal gastrectomy with D2 lymph node dissection was recommended as a standard surgery for distal gastric cancer patients. However, some controversy remains about the anastomosis of the residual stomach and the intestine. The objectives of this trial are to test the hypothesis that uncut Roux-en-Y anastomosis can reduce postoperative complications and improve n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The uncut Roux-en-Y anastomosisis restricts bile and duodenal uid from entering the residual stomach and reduces the possibility of alkaline re ux gastritis and esophagitis. Compared with Roux-en-Y anastomosis, uncut Roux-en-Y anastomosis keeps the continuity of jejunum structure, avoids the occurrence of ectopic pacers in jejunum and makes jejunum reverse peristalsis, reduces the occurrence of Roux Stasis Syndrome and improves the postoperative quality of life of patients [25][26] .In this study, RSS was not observed in the uncut Roux-en-Y anastomosis group.Gastroscopy was performed 1-year postoperative, the incidence of food retention, residual gastritis and bile re ux were 19.8% vs. 37.0%, 11.6% vs. 34.2% and 1.2% vs. 28.8% in the uncut Roux-en-Y anastomosis group and Billroth II with Braun anastomosis group, respectively,these differences were statistically signi cant differences(p<0.05).In addition, there were 2 cases of re ux esophagitis in the B-II with Braun anastomosis group,rate of 2.7%,There was no statistical signi cance between the two groups(p>0.05).Quality of life was evaluated by QLQ-C30 questionnaire 1-year postoperative, and there was no statistical signi cance in all scores(p>0.05). When evaluated by QLQ-STO22 questionnaire, the scores of pain and re ux symptom in the uncut Roux-en-Y anastomosis group were lower than those in the Billroth II with Braun anastomosis group, and the differences were statistically signi cant(P<0.05), indicating that there were fewer re ux and pain symptoms in the uncut Roux-en-Y anastomosis group and relatively good quality of life.In addition, in the B-II with Braun anastomosis group, residual gastritis and bile re ux was indicated in some patients, but no obvious clinical symptoms were found.…”
Section: Discussionmentioning
confidence: 67%
“…The uncut Roux-en-Y anastomosisis restricts bile and duodenal uid from entering the residual stomach and reduces the possibility of alkaline re ux gastritis and esophagitis. Compared with Roux-en-Y anastomosis, uncut Roux-en-Y anastomosis keeps the continuity of jejunum structure, avoids the occurrence of ectopic pacers in jejunum and makes jejunum reverse peristalsis, reduces the occurrence of Roux Stasis Syndrome and improves the postoperative quality of life of patients [25][26] .In this study, RSS was not observed in the uncut Roux-en-Y anastomosis group.Gastroscopy was performed 1-year postoperative, the incidence of food retention, residual gastritis and bile re ux were 19.8% vs. 37.0%, 11.6% vs. 34.2% and 1.2% vs. 28.8% in the uncut Roux-en-Y anastomosis group and Billroth II with Braun anastomosis group, respectively,these differences were statistically signi cant differences(p<0.05).In addition, there were 2 cases of re ux esophagitis in the B-II with Braun anastomosis group,rate of 2.7%,There was no statistical signi cance between the two groups(p>0.05).Quality of life was evaluated by QLQ-C30 questionnaire 1-year postoperative, and there was no statistical signi cance in all scores(p>0.05). When evaluated by QLQ-STO22 questionnaire, the scores of pain and re ux symptom in the uncut Roux-en-Y anastomosis group were lower than those in the Billroth II with Braun anastomosis group, and the differences were statistically signi cant(P<0.05), indicating that there were fewer re ux and pain symptoms in the uncut Roux-en-Y anastomosis group and relatively good quality of life.In addition, in the B-II with Braun anastomosis group, residual gastritis and bile re ux was indicated in some patients, but no obvious clinical symptoms were found.…”
Section: Discussionmentioning
confidence: 67%
“…Acid secretions can be readily controlled using proton-pump inhibitors and γ-aminobutyric acid (GABA) agonists, whereas bile salts and pancreatic secretions prove more difficult. 2 Failing medical management, patients with refractory symptoms require surgical reconstruction. 2…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, gastric jejunum Roux-en-Y anastomosis is one of the most commonly used surgical methods in the treatment of distal gastric malignancies due to its simple operation. However, due to the long operation time and the influence on the normal anatomical structure of the gastrointestinal tract, it has adverse effects on the postoperative antireflux of patients and severely regulates the quality of life and survival time of patients [ 8 , 9 ]. Gastric jejunum uncut Roux-en-Y anastomosis has gradually evolved into being the primary surgical treatment for clinical distal gastric malignancy through decades of continuous development since it was first reported in 1988 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%